Kinematic Movement Differences Between Petanque Pointing and Shooting Technique in Children - Nurhasan NURHASAN; Muchamad Arif Al Ardha; Kolektus Oky RISTANTO; Chung Bing YANG; Adi WIJAYANTO; Syahrudin Warta Kusuma Cucu PRADANA; Nur Salsabila Rhesa Pandhadha PUTRA; Awang FIRMANSYAH; Sauqi Sawa BIKALAWAN; Ainun Zulfikar RIZKI; Rizki Satrio UTOMO (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2024)
This study aimed to evaluate children's kinematic movement in petanque pointing and shooting techniques. There were 16 male beginner petanque athletes (aged 11.37 ± 1.36 years old, weight 42.37 ± 4.36 Kg, and height 151.37 ± 7.36 cm) who were selected using the purposive sampling method. The successful throwing was observed in the sagittal plane and measured by kinematic analysis in Kinovea 0.9.4 Software. There were pointing and shooting kinematic data, categorized into four phases, i.e., back swing, zero position, release, and follow throw position. As a result, there were significantly different in several variables of each phase between pointing and shooting techniques. There was a significant difference in the back swing phase at shoulder extension and ball height (α < .05). The shooting technique showed greater velocity (10.94 ± 13.34 m/s) than pointing (5.290 ± 0.44 m/s). In the release phase, every variable was significantly different (α < .05). The ball height in pointing was higher (92.53 ± 9.69 m) than in shooting (80.19 ± 10.74 m). Ball velocity at pointing was slower (6.46 ± 0.43 m/s) than shooting (16.09 ± 5.18 m/s). The release elevation angle at pointing was wider (42.38 ± 5.85 o) than shooting (35.31 ± 7.26 o). There were significant differences in trunk flexion, knee flexion, maximum ball height, and ball velocity at the follow-throw phase (α < .05). Ball velocity at pointing was slower (4.90 ± 2.35 m/s) than shooting (13.01 ± 5.36 m/s). In conclusion, the specific technique in shooting and pointing could be adapted in the training method for children to advance the result and successful possibility. Further study could be conducted in different age groups and gender to gain more information about the petanque throwing technique.